Influence of oil to digestive enzymes activity of cyprinids in subacute experiment - P. A. Kravetsky; I. V. Volkova; S. V. Shipulin (Юг России: экология, развитие)
Influence of crude oil to enzymatic systems of cyprinids in vivo was viewed in the article. Different localized enzymes of cyprinids with various nutrition types were investigated.